HISTORIOGRAPHY OF THE MATERIAL CULTURE OF THE KARAKALPAK PEOPLE. (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2024)
The people of Karakalpak have a special place among the peoples of the world with their rich culture since ancient times. The process of Karakalpak cultural learning has developed widely since the 20th century.